Pengaruh Motivasi Belajar Terhadap Kemampuan Berpikir Kritis Matematis Siswa - Jelita, Arni Asih; Isnaniah, Isnaniah; Yusri, Fadhilla; Imamuddin, M. (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The aim of this research is to determine the significant influence of learning motivation on the mathematical critical thinking abilities of class VII students at MTsN 11 Agam. The hypothesis in this research is